The association between sleep and cognitive abnormalities in bipolar disorder. Issue 1 (16th January 2019) - Bradley, A. J.; Anderson, K. N.; Gallagher, P.; McAllister-Williams, R. H.
Abstract: Background: Bipolar disorder (BD) is associated with attentional and processing abnormalities. Such abnormalities are also seen in healthy subjects with sleep disruption. We hypothesised cognitive abnormalities in BD patients would be worse in those with objectively verified sleep abnormalities. Methods: Forty-six BD patients and 42 controls had comprehensive sleep/circadian rhythm assessment over 21 days alongside mood questionnaires. Cognitive function was assessed with a range of tasks including Psychomotor Vigilance Test (PVT), Attention Network Task (ANT) and Digit Symbol Substitution Test (DSST). BD participants with normal and abnormal sleep were compared with age- and sex-matched controls. Results: BD patients had longer response times and made more lapses (responses >500 ms) than controls on the PVT (both p < 0.001). However, patients with normal sleep patterns did not differ from controls while those with sleep abnormalities did ( p < 0.001). An identical pattern of effects were seen with the ANT response times, with the abnormality in bipolar abnormal sleepers related to the executive attentional network. Similarly, patients made fewer correct responses on the DSST compared with the controls ( p < 0.001). Bipolar normal sleepers did not differ while those with abnormal sleep did ( p < 0.001). All these differences were seen in bipolar abnormal sleepers who were euthymic ( p < 0.01) and across the main abnormal sleep phenotypes. Conclusions: We confirm impairment in attention and processing speed in BD. Rather than sleep abnormalities exacerbating such dysfunction, the impairments were confined to bipolar abnormal sleepers, consistent with sleep disturbance being the main driver of cognitive dysfunction.